Monitoring Land Use and Land Cover Change Using GIS and Remote Sensing in the Mizewa Watershed, Upper Blue Nile Basin - Shiferaw, Abate; Anteneh, Mesfin; Haile, Fentanesh (Ethiopian Journal of Social Sciences, 2018)
The objective of this study is to evaluate the land use and land cover dynamics over  41 years (1973 to 2013) and to identify the major causes of changes in land use and land cover in the Mizewa watershed. The study used an integration of Remote Sensing (RS) and Geographic Information System (GIS) approach for analyzing the direction, magnitude, and spatial pattern of land use and land cover change in the study watershed. Results of this study showed that there were changes in land use and land cover patterns. Cultivated lands increased by 16.42% and 8.46% between 1973 to 1985 and 1986 to 1999 respectively. Furthermore, from 2000 to 2013, there were 1040.214, 984.028 and 111.02 hectares of settlement and plantation, bush lands and grasslands had been changed to cultivated land. The expansion of cultivated lands between 1973 and 2013 in the watershed could be directly related to rapid population growth and the  clearing of bush lands and grass lands for such increasing agricultural land demand. On the contrary, the size of shrub or bush lands and grass lands coverage had decreased from 1973 to 1985 with -17.18% and -39.79% with an annual rate of change of -1.32% and -3.07% respectively. In addition, settlement and plantation increased from 1985 to 1999 with a rate of 6.18% per year. However, grass lands and bush lands decreased from 1985 to 1999 with annual rate of change -0.78 and -2.11% respectively. The change was induced by the transformation of bush lands and grass lands to cultivated lands. The massive reduction of shrub or bush lands particularly between 1973 and 1985 occurred  due to lack of administration especially during the transition period and land redistribution as well as  drought. Shortage of land has forced farmers to cultivate steep slopes and shallow soils that are vulnerable to degradation, and to increasingly rely on selling firewood and charcoal for supplementary income which has also contributed to the extensive destruction of the woody biomass and shrub lands. The cumulative effect of these had resulted in environmental degradation. Hence, it is recommended that there should be appropriate land use planning that identifies the proper land for specific purpose so that the marginal lands will not be put into agricultural use.